Detections and constraints on white dwarf variability from time-series GALEX observations. Issue 4 (20th April 2019) - Rowan, D M; Tucker, M A; Shappee, B J; Hermes, J J
Abstract: We search for photometric variability in more than 23 000 known and candidate white dwarfs (WDs), the largest ultraviolet survey compiled for a single study of WDs. We use gphoton, a publicly available calibration/reduction pipeline, to generate time-series photometry of WDs observed by GALEX . By implementing a system of weighted metrics, we select sources with variability due to pulsations and eclipses. Although GALEX observations have short baselines (≤30 min), we identify intrinsic variability in sources as faint as Gaia G  = 20 mag. With our ranking algorithm, we identify 48 new variable WDs in archival GALEX observations. We detect 40 new pulsators: 36 have hydrogen-dominated atmospheres (DAVs), including one possible massive DAV, and four are helium-dominated pulsators (DBVs). We also detect eight new eclipsing systems; five are new discoveries, and three were previously known spectroscopic binaries. We perform synthetic injections of the light curve of WD 1145+017, a system with known transiting debris, to test our ability to recover similar systems. We find that the 3σ maximum occurrence rate of WD 1145+017-like transiting objects is $\le 0.5{{\ \rm per\ cent}}$ .